The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/13235818.2017.1279476
|View full text |Cite
|
Sign up to set email alerts
|

The genusPotamolithusPilsbry, 1896 (Gastropoda: Tateidae) on the Somuncurá Plateau, Patagonia, Argentina

Abstract: The genus Potamolithus (Gastropoda: Tateidae) is endemic to South America where it is distributed mainly in the Ribeira, Itajaí-açú and Jacuhy Rivers in southern Brazil and the Uruguay River, part of the Paraná and Río de la Plata drainage systems. An exception to the pattern of distribution is Potamolithus valchetensis Miquel, 1998, which is endemic to the Valcheta Stream, Somuncurá Plateau, Patagonia, Argentina. Here we provide a review of Potamolithus from this plateau based on new samples and review of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The minute native gilled freshwater snails in Chile, at present placed in the genera Littoridina, Heleobia or Potamolithus, have had a complicated taxonomic history, as they have been ascribed to the families Amnicolidae, Hydrobiidae, Littoridinidae and Cochliopidae (e.g., Pilsbry 1911;Biese 1944Biese , 1947Hershler & Thompson 1992;Valdovinos 1999Valdovinos , 2006Figueroa et al 1999;Sielfeld 2001). In Argentina, the taxonomic position of some species traditionally recognized as representatives of the genus Heleobia (Cochliopidae) as members of the family Tateidae has recently been discussed by different authors (Koch et al 2015;de Lucía & Gutiérrez Gregoric 2017). In the present study, the tree-based barcoding analysis provided evidence to transfer Littoridina/Heleobia santiagensis to the genus Potamolithus (Tateidae).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The minute native gilled freshwater snails in Chile, at present placed in the genera Littoridina, Heleobia or Potamolithus, have had a complicated taxonomic history, as they have been ascribed to the families Amnicolidae, Hydrobiidae, Littoridinidae and Cochliopidae (e.g., Pilsbry 1911;Biese 1944Biese , 1947Hershler & Thompson 1992;Valdovinos 1999Valdovinos , 2006Figueroa et al 1999;Sielfeld 2001). In Argentina, the taxonomic position of some species traditionally recognized as representatives of the genus Heleobia (Cochliopidae) as members of the family Tateidae has recently been discussed by different authors (Koch et al 2015;de Lucía & Gutiérrez Gregoric 2017). In the present study, the tree-based barcoding analysis provided evidence to transfer Littoridina/Heleobia santiagensis to the genus Potamolithus (Tateidae).…”
Section: Discussionmentioning
confidence: 57%
“…An initial BLASTn-analysis against the data base of GenBank confirmed that the species in question belonged to Tateidae. We also performed a Bayesian tree-based barcoding approach (Erickson & Driskell 2012) to assess the familial/generic allocation of the species analyzed together with representative species of these families retrieved from GenBank (Hershler et al 1999;Haase 2005;Kroll et al 2012;Hamada et al 2013;Wilke et al 2013;Koch et al 2015;Collado et al 2016a;de Lucía & Gutiérrez Gregoric 2017;Colgan & da Costa, unpublished data). As COI was highly saturated across both families as shown by the test of Xia et al (2003), our analysis was not supposed to reflect accurate relationships, but it allowed us to assign the Chilean species to their respective families and genera.…”
Section: Methodsmentioning
confidence: 99%
“…Posterior probabilities (>0.94) values are indicated at the nodes. Numbers after taxa names indicate GenBank access numbers 20–22,25,32,38,87,101106 (Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…However, non-native mudsnail populations are composed typically of parthenogenetic females, with males being rare or absent 23,43,85,86 . Genus Potamolithus is dioecious, the penis is simple, variable in pigmentation among taxa 8792 ; the females of some species develop a nuchal node 88–90 . In contrast to Heleobia and Potamolithus , whose species are oviparous 18,19,82,93,94 , the mudsnail is ovoviviparous, with females brooding small juvenile in the pallial oviduct 25,26,32,33,41 .…”
Section: Methodsmentioning
confidence: 99%
“…Cretaceous record of Tateidae Forasiepi & López Armengol (1999) mentioned the presence of Potamolithus windhauseni (Parodiz, 1961) for the Los Alamitos Formation (Campanian -Maastrichtian) from Río Negro Province, Argentina. The genus has a restricted areal distribution in South America, comprehending the Río de la Plata basin and relict populations in southern Argentina and Chile (Miquel, 1998;de Lucía & Gutiérrez Gregoric, 2017). The specimens here described constitute the southern-most record of Potamolithus.…”
Section: Superfamily Truncatelloidea Gray 1840mentioning
confidence: 99%